Decolourization Kinetics of Congo Red Using Immobilized and Free Cells of Rhodococcus biphenylivorans - Maegala Nallapan Maniyam; Primeela Gunalan; Hazeeq Hazman Azman; Hasdianty Abdullah; Nor Suhaila Yaacob (Brazilian Archives of Biology and Technology)
Abstract In the present study, a cost-effective and eco-friendly approach is being explored to remove the harmful dye Congo red from synthetic wastewater, using an equatorial strain of Rhodococcus biphenylivorans. The immobilized cells’ Congo red-decolorizing activity in calcium alginate showed an increase of 217% compared to the free cells. By improving the alginate concentration to 4% (w/v), the bead diameter to 3 mm and using 50 beads, a 67% decrease in the time required for complete decolorization was accomplished. Both free and immobilized cells followed first-order kinetics for the elimination of Congo red, with immobilized cells displaying a decolorization rate 3.2 times greater than that of free cells, resulting in an 84% reduction in half-life. The immobilized cells displayed the capability to remove 0.10 g/L Congo red without any significant decline in their efficiency for up to twelve cycles, offering an economic advantage due to their reusability. Examining the decolorized products of Congo red showed no hindrance in the germination of Triticum aestivum and Vigna radiata, indicating the effective removal of all toxic components from the original dye via the biological method. Therefore, this strain has significant potential as a biological agent to eliminate wastewater contaminated with Congo red efficiently.